2009
DOI: 10.1007/s11240-009-9575-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reducing sugar concentration on in vitro tuber formation and sprouting in yam (Dioscorea cayenensis–D. rotundata complex)

Abstract: The effects of reducing sucrose level on tuber formation (% of cultures with microtubers), development (length and fresh weight of microtubers) and sprouting in yam Dioscorea cayenensis-D. rotundata complex in vitro were investigated. Only 29% of the explants showed tuber formation after 3 weeks in the presence of 1% sucrose in contrast to 100% with 3%. After 120 days of culture, the length and the weight of the tubers obtained in the presence of 1% sucrose were less than with 3% sucrose. Addition of sorbitol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…La sécurité alimentaire et la lutte contre la pauvreté constituent une préoccupation de la plupart des pays du monde (Ondo, 2009). Dans plusieurs pays de l'Afrique subsaharienne, l'agriculture est un secteur majeur de l'économie et son intensification et diversification restent une priorité (Eromosele et al, 2008).…”
Section: Introductionunclassified
“…La sécurité alimentaire et la lutte contre la pauvreté constituent une préoccupation de la plupart des pays du monde (Ondo, 2009). Dans plusieurs pays de l'Afrique subsaharienne, l'agriculture est un secteur majeur de l'économie et son intensification et diversification restent une priorité (Eromosele et al, 2008).…”
Section: Introductionunclassified
“…Thus, the mini-rhizome and microrhizome formation in response to sugar classes and concentration in the culture medium depends on plant species. Tuber formation, size and fresh weight in acclimatized plantlets of yam under 3% sucrose was maximized after transplanting for 60-120 day (Ovono et al 2009), whereas 6% sucrose or 8% maltose was required for cocoyam (Xanthosoma sagittifolium) for mini-tuberization (Djeuani et al 2014). The secondary metabolites, BIS, DEM and CUR, in mini-rhizomes of wild turmeric plantlets acclimatized under 3% sucrose were highest, whereas micro-rhizome formation (>50%) and fresh weight (>0.025 g) were maximized in 5-9% sucrose (Wu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, an increase in the level of AGPase has been shown to enhance biomass and yield in cassava tubers (Ihemere et al, 2006). Sucrose is not only one of the main photoassimilates but also a driving force for the formation and growth of TR (Ovono et al, 2009). It has been reported that a high sucrose level is required for in vitro induction of TR in sweetpotato (Tsubone et al, 2000).…”
Section: Introductionmentioning
confidence: 99%